Comparison of non-invasive tear film stability measurement techniques - Wang, Michael Tm; Murphy, Paul J; Blades, Kenneth J; Craig, Jennifer P (Clinical and experimental optometry, 2018)
Measurement of tear film stability is commonly used to give an indication of tear film quality but a number of non-invasive techniques exists within the clinical setting. This study sought to compare three non-invasive tear film stability measurement techniques: instrument-mounted wide-field white light clinical interferometry, instrument-mounted keratoscopy and hand-held keratoscopy. Twenty-two subjects were recruited in a prospective, randomised, masked, cross-over study. Tear film break-up or thinning time was measured non-invasively by independent experienced examiners, with each of the three devices, in a randomised order, within an hour. Significant correlation was observed between instrument-mounted interferometric and keratoscopic measurements (p < 0.001) but not between the hand-held device and the instrument-mounted techniques (all p > 0.05). Tear film stability values obtained from the hand-held device were significantly shorter and demonstrated narrower spread than the other two instruments (all p < 0.05), while no significant differences were observed between the two instrument-mounted devices (all p > 0.05). Good clinical agreement exists between the instrument-mounted interferometric and keratoscopic measurements but not between the hand-held device and either of the instrument-mounted techniques. The results highlight the importance of specifying the instrument employed to record non-invasive tear film stability.